A Dictated Space? Women and Their Well-being in a Kerala Village. (October 2014) - Scaria, Suma
The mainstream theories on development try to understand the empowerment of women through select indicators relating to education and health. Kerala provides a suitable setting to understand how far higher levels of literacy, enrolment in higher education, favourable sex ratio, small family and access to health care facilities translate into empowerment of women defined in terms of their role in decisionmaking within a household and freedom of physical mobility. Our findings based on the micro-level study of a village in Kerala reveal that remarkable achievements measured by conventional indicators have failed to elevate women from their subordinate status within a household. The analysis of Kudumbashree, a state-sponsored woman-centric poverty alleviation programme, also reveals that women's access to community programmes has failed to empower them. Such an apparent paradox is explained through a complex process of gendering at three levels: education, employment and access to economic resources. Social norms, the dowry system, the patrilineal system of inheritance and patrilocal residence also affect such a gendering process. The choices that a woman/household makes regarding her education, activity pattern and community participation are very much shaped by a gendered social structure where a man is associated with 'outside activity' and woman with 'inside activity'.